RANCANG BANGUN APLIKASI PENCARIAN LAUNDRY BERBASIS ARSITEKTUR MICROSERVICE MENGGUNAKAN METODE RAD - Vania, Rekha; Aljabar, Andi (Pusat Riset dan Inovasi Nasional, 2024)
Laundry is a business engaged in providing service services, including washing, ironing, and so on. The options for laundry services nowadays are diverse, ranging from clothing, blankets, carpets, shoes, to helmets. Laundry services have rapidly expanded in various locations in the Cibinong area. However, the widespread presence of laundries coupled with a lack of internet-connected information poses difficulties for individuals in urgent need, making it challenging to find the exact and fast location of laundry services. Therefore, the author has designed and developed an application to facilitate the public in quickly and efficiently finding information and locations of laundry services. The author utilized the Java programming language for building the Android application, with PHP serving as the backend. Microservice architecture was employed, dividing the system into small services, and the Rapid Application Development method was adopted as the development approach. Blackbox testing was used as the testing method.